Pack up the moon - Higgins, Kristan (Berkley, 2021)
"Twelve letters. That's what Lauren decides to leave her husband when she finds out she's dying. Twelve letters to see him through the first year without her, and to lead him on a heartrending, beautiful, often humorous journey to find happiness again in the new novel from New York Times bestselling author Kristan Higgins."--